The Impact of Knowledge Sharing on Organizations and How to Overcome It During the COVID-19 : A Systematic Literature Review - Rizaldy Septa Amanda; Hidayat Akbar; Dana Indra Sensuse; Nadya Safitri (Ridwan Institute, 2023)
Many of the challenges that organizations face during the COVID-19 pandemic are how to effectively share, and manage access, acquisition, and storage of knowledge in their individuals, teams, and the organization as a whole. It is important for organizations to respond to new global risks and catastrophic extra-organizational events and crises such as the current COVID-19 pandemic by leveraging knowledge management and innovation created through technology-based knowledge sharing. The purpose of this study is to collect, summarize, analyze systematically and synthesize information about knowledge sharing impact in organization during pandemic era and what techniques the company uses to deal with those impacts by providing systematic literature review that have been done by researchers previously. The results of this study explain the most impact of knowledge sharing that occurs on the organization during pandemic era and there some techniques to use for examining the impact of knowledge sharing in the organization.